2020
DOI: 10.1016/j.ijpsycho.2020.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nicotine on pupil size and performance during multiple-object tracking in non-nicotine users

Abstract: Nicotine has been commonly used in pyschopharmacological studies, showing its benefits as a pharmacological stimulant on cognitive performance. In the current study, we investigated the effects of 2 mg (Experiment 1) and 4 mg (Experiment 2) of nicotine on performance on a multiple-object-tracking task. Participants were young non-smoking adults with no pre-existing attentional deficits. Nicotine and placebo were administered through nicotine and nicotinefree taste-matched chewing gum, respectively. Additionall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…In addition, Bayesian analyses provided support for the absence of these relationships in all analyses. Further, a Bayesian regression analysis indicated that nicotine consumption was a better predictor of average baseline pupil size than any of the task scores (see also Wardhani et al, 2020).…”
Section: Discussionmentioning
confidence: 94%
“…In addition, Bayesian analyses provided support for the absence of these relationships in all analyses. Further, a Bayesian regression analysis indicated that nicotine consumption was a better predictor of average baseline pupil size than any of the task scores (see also Wardhani et al, 2020).…”
Section: Discussionmentioning
confidence: 94%
“…The average pupil diameter was similar in the two groups (4.7mm for smokers vs 4.56mm for controls, t (37.66) = 0.462, p = 0.647). Note that the acute effects of nicotine intake are known to globally constrict the pupils (Wardhani et al, 2020), but we asked all participants to refrain from smoking prior to the experiment. At any rate, in order to better cope with individual (and group) differences we z-tranformed pupil diameter values separately for each participant (Dureux et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Most of them were light smokers, however, as seen by low average scores (1.96 ± 2.1) at the Fagerström test for Nicotine Dependence (FTND; Heatherton et al, 1991). Because nicotine can considerably reduce pupil size (Wardhani et al, 2020), and because we sought to evaluate the tasks in conditions of relative craving, they were all asked to refrain from smoking for at least 90 minutes prior to the experiment (mean: 7.5 hours; indeed, half of them last smoked the evening before the experiment). In addition to the FTND, smokers were asked to fill in the Severity of Dependence Scale (SDS; Gossop et al, 1992) and the Questionnaire of Smoking Urges (QSU-brief; Cox et al, 2001), to assess self-reported craving.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nicotine potentiates cognitive functions due to its action on the cortex, frontal and parietal areas, the anterior cingulate, and the superior colliculus. This effect has been appreciated, particularly in those with nicotine dependency, who receive nicotine after a deprivation period 12 .…”
Section: Nicotine Is a Powerfully Addicting Drug: Neurophysiology Of ...mentioning
confidence: 99%